Benchmarking best practices in maintenance management - Wireman, Terry (Industrial Press, 2010)
Thoroughly revised and updated, this best selling book presents a logical, step-by-step methodology that will enable any company to conduct a cost-effective benchmarking effort. It presents an overview of the benchmarking process, a detailed form for surveying and 'grading' maintenance management, and a database of the results of more than 100 companies that have used this survey. This title provides a clear, concise benchmarking methodology. It clearly explains and interprets the most current maintenance benchmarks. It contains a benchmarking database from more than 100 companies. It features current maintenance/asset management philosophies. It offers more information on self-analysis.